Principais métodos de diagnóstico para degeneração valvular mixomatosa em cães: revisão sistemática - Santos, Jady Franciele da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The myxomatous valvular degeneration is a common disorder in small-breed old dogs, and is characterized by several structural changes in the heart valves. Numerous tests can demonstrate these changes, nonetheless, there is disagreement about its final diagnosis. The main goal of this paper was to describe the foremost methods of diagnosis of myxomatous valvular degeneration in dogs, as well as to evaluate their effectiveness. A systematic review was made by using 10 selected articles from Scielo databases, Periódicos CAPES, PubMed and Google Scholar. The search strategy was as follows: (degenerative valve disease) OR (chronic valvular disease) OR (myxomatous valve degeneration) OR (chronic valvular fibrosis) OR (chronic degenerative valve disease) OR (endocardiosis) AND (dogs). The articles included were written in Portuguese and English, with no publication year restriction and were classified according to the quality scale of Jadad et al. (1996) and the Degree of Recommendation and Level of Scientific Evidence. The diagnostic methods were analyzed for their efficacy, and the author's opinion and conclusion were compared. The echocardiogram was considered a gold standard for diagnosis. Radiography and cardiac auscultation were considerable viable as an auxiliary diagnostic method. Electrocardiography showed questionable efficacy. The quantification of inflammatory mediators and cardiac biomarkers have shown promising results, although additional studies are needed.

A degeneração valvular mixomatosa é uma enfermidade comum em cães senis de raças de pequeno porte, e se caracteriza por diversas alterações estruturais das válvulas cardíacas. Existem vários exames que são capazes de demonstrar essas alterações, mas há uma divisão de opiniões quanto ao seu diagnóstico definitivo. O objetivo desse trabalho foi descrever os principais métodos de diagnóstico da degeneração valvular mixomatosa em cães, assim como avaliar sua eficácia. Foi realizada uma revisão sistemática utilizando 10 artigos selecionados dos bancos de dados Scielo, Periódicos CAPES, PubMed e Google Acadêmico. A estratégia de busca foi a seguinte: (degenerative valve disease) OR (chronic valvular disease) OR (myxomatous valve degeneration) OR (chronic valvular fibrosis) OR (chronic degenerative valve disease) OR (endocardiosis) AND (dogs). Os artigos inclusos eram dos idiomas português e inglês, sem restrição de ano de publicação e foram classificados conforme a escala de qualidade de Jadad et al. (1996) e o Grau de Recomendação e Nível de Evidência Científica. Os métodos de diagnósticos foram analisados quanto sua eficácia, e a opinião e conclusão dos autores foram comparadas. O ecocardiograma foi considerado padrão ouro de diagnóstico. A radiografia e a auscultação cardíaca foram consideradas viáveis como método auxiliar de diagnóstico. A eletrocardiografia apresentou eficácia questionável. A quantificação de mediadores inflamatórios e biomarcadores cardíacos revelaram resultados promissores, porém necessitam mais estudos.
Keywords: Cardiologia veterinaria; Coração - Válvulas - Doenças; Ecocardiografia; Auscultação; Cães; Myxomatous valvular degeneration